Normas técnicas de informação e documentação: Abnt versus Vancouver - Bertholino, Maria Luzia Fernandes; Silva, Vera Lucia Braga da (My University, 2008)
O artigo ressalta a importância da padronização dos trabalhos cientíﬁcos e a valorização da normalização para a divulgação e comunicação da informação cientíﬁca. Apresenta um breve histórico das normas e padrões da Associação Brasileira de Normas Técnicas (ABNT) e da norma editada pelo grupo de Vancouver, destacando as divergências identiﬁcadas em cada uma delas. Espera-se que haja um consenso de uniformização de padrões na comunicação cientíﬁca.

The article highlights the importance of the standardization of scientiﬁc works and the value of normalization for the divulgation and communication of scientiﬁc information. It presents a brief history of the “Brazilian Association of Technical Norms” (ABNT) rules and standards, and of the “group of Vancouver” edited norms, detaching the divergences between them. It is expected that a consensus for standardization is achieved for the scientiﬁc communication.
Techniques norms of information and documentation: Abnt versus Vancouver
Keywords: Normas Técnicas; Informação e documentação; ABNT; Vancouver